2012
DOI: 10.4314/sajas.v42i5.8
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition and oxidative stability of lambs’ meat as affected by a bioflavonoid antioxidant and fat sources

Abstract: ________________________________________________________________________________ AbstractA study was conducted to investigate the effects of a synthetic or natural antioxidant and fat saturation, in a standard feedlot diet, on fatty acid composition and oxidative stability of lamb. The four dietary treatments consisted of the same basal diet providing 187 g crude protein (CP), 355 g neutral detergent fibre (NDF), and 71 g ether extract (EE) per kg dry matter (DM), differing in fat source (30 g/kg of either sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Thus, there is an increased interest in research on ways to modify the fatty acid composition of ruminant meat, especially in ways to reduce the concentration of SFAs and increasing that of PUFAs (Nieto and Ros ). The fatty acid profile of lamb meat can be favorably manipulated by altering the source of the fat included in the diet (Lee and others ; Booyens and others ). The complexity of ruminant digestion is determined mainly by its symbiotic ruminal microbiota, and this complexity will continue to challenge efforts to modulate meat quality, including its fatty acid composition (Bessa and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is an increased interest in research on ways to modify the fatty acid composition of ruminant meat, especially in ways to reduce the concentration of SFAs and increasing that of PUFAs (Nieto and Ros ). The fatty acid profile of lamb meat can be favorably manipulated by altering the source of the fat included in the diet (Lee and others ; Booyens and others ). The complexity of ruminant digestion is determined mainly by its symbiotic ruminal microbiota, and this complexity will continue to challenge efforts to modulate meat quality, including its fatty acid composition (Bessa and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the differences in the FA profiles of the current experimental diets, none of the individual FAs in the meat was affected by the dietary BT (Table 4). This was not observed in another study, where inclusion of saturated tallow (30 g/kg DM) resulted in higher lamb muscle content of palmitoleic acid (C16:1c9) and monounsaturated fatty acids (MUFAs) (Booyens et al, 2012). One explanation for the lack of effect of dietary BT on fatty meat FA profile might be that FAs originating from BT are in the free form and not bound within triacyl glycerol molecules (Siebrits et al, 2009).…”
Section: Resultsmentioning
confidence: 83%
“…In sheep, two studies have evaluated the effects of replacing grains with BT on growth of finishing lambs, finding variable effects of 20 and 40 g BT/kg DM on average daily gain (ADG) and feed conversion (Ružić-Muslić et al, 2009;Ahmed et al, 2015). Booyens et al (2012) also indicated the possibility of altering the FA profile of meat from lambs by feeding different sources of fat. When supplemental fat replaces grains and byproducts the formulation of the entire diet should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in meat FAs composition due to lipid supplementation are dependent on the FA pro le of the supplement, amount of lipid supplemented in the diet, form of lipid in the diet, processing of oilseeds, composition of the basal diet and duration of feeding supplement (Chikwanha et al 2018). Despite the microbial biohydrogenation in the rumen which extensively impacts the pro le of FAs deposited in body tissues; the FAs pro le of lamb meat can be favorably manipulated by altering the source of the fat included in the diet (Booyens et al 2012). Beside different processing methods to protect FAs from ruminal biohydrogenation, whole seeds may offer degrees of protection as the protein coat of oil bodies forms a barrier limiting biohydrogenation (Chikwanha et al 2018).…”
Section: Discussionmentioning
confidence: 99%